Klasifikasi Penjualan Perhiasan Menggunakan Metode Decision Tree Algoritma C4.5 (Studi Kasus: Toko Emas Berkat Famili) - Herizal Syafputra; Herlina Latipa Sari; Khairil Khairil (UNIVED Press, 2024)
Jewelry sales classification using Decision Tree Method with C4.5 Algorithm at Berkat Famili Gold Shop can facilitate and assist the store in obtaining information on the classification of sales of goods that are most in demand (in demand) and those that are less in demand (less in demand) from the results of sales data processing. The aspects or attributes used as parameters for the classification process are item type, item name, price, weight per gram, grade, inventory, sales, and sales status. Of the 14 test data used, the results of rule formation were obtained as many as 8 rules. Based on the results of rule formation, it is obtained that the most popular items (in demand) are Indian earrings, plain rings, rice necklaces, crystal earrings if the price is more than Rp. 726667, model rings if the weight is more than 2gram. Based on the system tests that have been carried out, it can be concluded that the functional of the jewelry sales classification application at Berkat Famili Gold Shop can has run well and can provide the results of the classification of sales of goods automatically through the C4.5 Method.